Tourism communication strategy for economic growth through music concerts - Paramita, Sinta; Aulia, Sisca; Rusdi, Farid; Mutongi, Chipo (Manajemen Komunikasi, 2025)
This research is urgent because international music concerts are now recognized as economic drivers, not just entertainment, as the Indonesian music industry shows signs of recovery following the pandemic. Further development will test the music concert tourism communication model derived from previous research to validate its potential. The purpose of this research is to determine how the Music Concert Tourism Communication Model can be applied to Indonesian society. The theoretical approach used in this research is the music concert tourism communication model. The method employed is a qualitative approach, utilizing a case study method that involves data collection techniques such as focus group discussions and descriptive surveys. The results show that the micro, meso, and macro elements of the music concert tourism communication model are important factors in improving the economic sector. The Merdekafest concert successfully attracted thousands of domestic and international tourists, resulting in a surge in demand for accommodation, transportation, culinary, and retail services. Local business actors were involved in the event's supply chain, from logistics to merchandise sales and distribution. However, other factors, such as terrorist threats and pandemics, can hinder this model, necessitating the implementation of tourism protocols in such cases. By mastering communication mechanisms, future international music concerts can make a more significant contribution to economic progress. The implications of this study provide valuable insights to inform government plans for investing in the music industry, particularly international music concerts, and offer hope for the industry's recovery.